1992
DOI: 10.5014/ajot.46.8.751
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Occupational Therapy: A Critical Reflection

Abstract: In the Netherlands, Dutch health care professionals, including occupational therapists, are confronted with a growing number of patients whose cultural backgrounds differ from theirs. Acknowledging this influx, the Dutch government allocated a grant for educating occupational therapy students on cross-cultural care. This paper summarizes the information we collected from a survey of Dutch occupational therapists on treatment of immigrants and briefly describes the eight educational tools we developed for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 3 publications
3
77
0
4
Order By: Relevance
“…Some excellent examples are: talking about diverse groups in an informal discussion format, case studies discussion, simulation games (for example, exercises in culture shock, role-playing), a critical essay on the white middle-class values and norms that underlie occupational therapy theory and practice (Kinebanian and Stomph, 1992), and interaction with a person who is knowledgeable about two cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some excellent examples are: talking about diverse groups in an informal discussion format, case studies discussion, simulation games (for example, exercises in culture shock, role-playing), a critical essay on the white middle-class values and norms that underlie occupational therapy theory and practice (Kinebanian and Stomph, 1992), and interaction with a person who is knowledgeable about two cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive curricula as proposed by Kinebanian and Stomph (1992) and MacDonald and Rowe (1995) aiming to develop cultural understanding and sensitivity of occupational therapy students toward different ethnic groups are of importance to the profession. Sue (1991) suggests that training programmes should contain an awareness and knowledge component (for example, lectures and readings on a variety of cultures), an affective component (for example, debriefing and reflecting regarding feelings of another culture through informal discussion), and a skills component (for example, an in-depth personal interaction with another culture for an extensive period of time).…”
Section: Discussionmentioning
confidence: 99%
“…Out group antagonism and marginalisation of outsiders as barrier for newcomers 16 Weltin et al 36 Specific, objective, external conditions that enable one to seek care, such as having health insurance. Garden, location/ accessibility, face-to-face meetings, easy travel distance, encouragement (diabetic nurse) educator, reasonable advice, social and cultural support…”
Section: Discussionmentioning
confidence: 99%
“…15 Occupational therapists have also shown more interest in studying immigrants' occupational life, which in turn informs their intervention plans. 16 There seem to be some occupational therapy programmes across different countries with a considerable immigrant population that study issues around immigrants' occupational life and participation in a variety of life situations. 17 Up until now previous studies within the field of occupational therapy, in particular mental health, have shown several shortcomings in providing optimum intervention to immigrant clients, due to differences in world views between clients and staff about the concept of occupation, participation and their potential values.…”
mentioning
confidence: 99%
“…Há pesquisadores dedicando-se às questões circundadas à mobilidade humana, sejam no âmbito das migrações, situações de refúgio ou de descolamentos devido às catástrofes naturais. Na literatura internacional, os estudos têm se voltado principalmente para a educação e saúde, saúde mental e saúde da mulher (DYCK, 1992;KINÉBANIAN;STOMPH, 1992 Savadogo (2014), Barros (2010Barros ( , 2015, Pierote-Silva (2014), em diferentes vertentes de pesquisa, tematizando, respectivamente, a mobilidade estudantil, religiosidade e busca de conhecimento, e a reflexão sobre mobilidade e dos direitos humanos. Nestes estudos, a cultura enquanto modo de vida, formas relacionais, ética, estética e de expressões do sagrado que criam sentidos, pertencimentos e identidades, é eixo organizador das reflexões e das metodologias de ação e construção de conhecimento em terapia ocupacional.…”
Section: Cultura E Mobilidade Humana: Desafio Contemporâneo Para a Teunclassified